Cognitive impairment in a patient with COVID‐19 on hemodialysis: Too dangerous to neglect!. Issue 4 (16th June 2021) - Jacobs, Lucas M.; Gazagnes, Marie Dominique; Sanoussi, Said; Collart, Frederic; Mesquita, Maria do Carmo F.
Abstract: Neurological manifestations of coronavirus disease 2019 (COVID‐19) often have tragic repercussions. Although many reports of neurological complications of severe acute respiratory syndrome coronavirus 2 infection exist, none of them are of patients on hemodialysis, who have a fivefold greater risk of stroke than the general population. In this report, we emphasize the importance of being vigilant for mild stroke in high risk populations—such as patients on hemodialysis—with COVID‐19, since these conditions have overlapping symptoms.